Cover Feature: The 1, 6, 7, 12‐Tetraazaperylene Bridging Ligand as an Electron Reservoir and Its Disulfonato Derivative as Redox Mediator in an Enzyme–Electrode Process (Chem. Eur. J. 62/2017). Issue 62 (18th September 2017) - Brietzke, Thomas; Dietz, Thomas; Kelling, Alexandra; Schilde, Uwe; Bois, Julianae; Kelm, Harald; Reh, Manuel; Schmitz, Markus; Körzdörfer, Thomas; Leimkühler, Silke; Wollenberger, Ulla; Krüger, Hans‐Jörg; et al.
Abstract : Complex dication [Ru(L‐N4 Me2 )2 μ‐tape‐(SO3 )2 ] 2+ ([4 ] 2+ ) was exploited as a redox mediator between an anaerobic homogenous reaction solution of an enzyme system (sulfite/sulfite oxidase) and the electrode by participation of the low‐energy π*‐orbital of the disulfonato‐substituted bridging ligand tape–(SO3 )2 2− . Tape diruthenium complexes could be a new valuable group of artificial redox mediators. The redox potential of these complexes can be easily modified for the required purpose by different substituents at the bridging tape and the terminal macrocycle. More information can be found in the Communication by H.‐J. Krüger, H.‐J. Holdt et al. onpage 15583 .